Stability enhancement of MWCNT/water nanofluids using PVA surfactant - Rashidi, Saba; Abdullah, Luqman Chuah; Walvekar, Rashmi Gangasa; Mohammad Khalid; Razi, A. Fakhrul; M. Y., Faizah (Inderscience Publishers, 2020)
Nanofluids are prepared by dispersing MWCNT into aqueous polyvinyl alcohol (PVA) suspensions used as base fluids. This paper investigates the effectiveness of PVA as surfactant in stabilising MWCNT/water nanofluids. The stability of nanofluids is measured by Zetasizer Nano-ZS of only the stable samples. The morphology of carbon nanotube (CNT) and its interaction with PVA dispersant was analysed using SEM and in order to observe the dispersion characteristics of all samples, image analysis was carried out using TEM. The results demonstrated that zeta potential is affected by the concentration of CNT (0.01-0.1 wt.%). The zeta potential values (-19.96 mV to -33.3 mV) increased with an increase in CNT concentration. The SEM and TEM results showed that the amount of PVA added to each CNT concentration is sufficient to provide maximum stability to the CNT-water nanofluids, no excessive agglomerations or significant clusters of PVA are observed from the surface of CNT.